EFFECT OF SOME ANTIOXIDATS (ASCORBIC ACID, PROLINE, AND SALIC ACID) ON JOJOBA PLANTS UNDER CIRCUMSTANCE OF SINAI - & et al., Khattab (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Two field experiments of jojoba plants were carried out in Almaghara Research and Production Station followed to Desert Research Center, Agriculture Ministry, North Sinai Governorate, Egypt, at 2016/2017 and 2017/2018, Respectively. Therefor to study the influence yield of five clones (S-L, S-610, S- 700, S-B and S-G) under foliar spray of salicylic acid, ascorbic acid and proline [(50:50:50(conc. 1); 100:100:100 (conc. 2) and 200:200:200 ppm (conic. 3)] on jojoba plants at four and fourteen years old from planting.  The experiment was conducted as split plot design, were varieties order in the main plots and treatments in sub plots, uisg three replicates. esults showed that the foliar application of salicylic acid, ascorbic acid and proline led to increase of all growth characters, yield characters and some chemical contents in leaves and seeds on all of clones. Clones S-700 recoded the highest values for all traits studied followed by clones S-B, while, studied traits, clones S-L recorded the lowest values. Foliar spray application with salicylic acid, ascorbic acid and proline had the highest data with all clones with aged fourteen years compear aged four years. All characters increased with increase in salicylic acid, ascorbic acid and proline on varieties, especially clone S-700. Jojoba plants appearance response to plant nutrition.